New Approaches for the Discovery of Pharmacologically-Active Natural Compounds - Medina-Franco, José L. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
A major source of active compounds, natural products from different sources supply a large variety of molecules that have been approved for clinical use or used as the starting points of optimization programs. This book features nine papers (eight full articles and one review paper) written by more than 45 scientists from around the world. These papers illustrate the development and application of a broad range of computational and experimental techniques applied to natural product research. On behalf of the contributors to the book, our hope is that the research presented here contributes to advancements in the field, and encourages multidisciplinary teams, young scientists, and students to further advance in the discovery of pharmacologically-active natural compounds